2018
DOI: 10.1097/aln.0000000000002192
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Drug-related and State-related Effects of Dexmedetomidine and Propofol on the Electroencephalogram

Abstract: Background Differentiating drug-related changes and state-related changes on the electroencephalogram during anesthetic-induced unconsciousness has remained a challenge. To distinguish these, we designed a rigorous experimental protocol with two drugs known to have distinct molecular mechanisms of action. We hypothesized that drug- and state-related changes can be separated. Methods Forty-seven healthy participants were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 34 publications
1
45
1
Order By: Relevance
“…These dexmedetomidine Ce values were similar to those reported by Colin et al, which were 0.43, 0.79 and 1.34 ng/mL at MOAA/S ≤ 4, 3 and 2, respectively, in volunteers in a silent environment. Although the estimated Ce 50 values of sedation scales in patients have not been reported yet, other studies have shown comparable ranges of dexmedetomidine plasma concentration . Scheinin et al documented the deep sedative concentration of dexmedetomidine as 1.36 ng/mL in plasma.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…These dexmedetomidine Ce values were similar to those reported by Colin et al, which were 0.43, 0.79 and 1.34 ng/mL at MOAA/S ≤ 4, 3 and 2, respectively, in volunteers in a silent environment. Although the estimated Ce 50 values of sedation scales in patients have not been reported yet, other studies have shown comparable ranges of dexmedetomidine plasma concentration . Scheinin et al documented the deep sedative concentration of dexmedetomidine as 1.36 ng/mL in plasma.…”
Section: Discussionmentioning
confidence: 98%
“…Although the estimated Ce 50 values of sedation scales in patients have not been reported yet, other studies have shown comparable ranges of dexmedetomidine plasma concentration . Scheinin et al documented the deep sedative concentration of dexmedetomidine as 1.36 ng/mL in plasma. In the present study, a higher dexmedetomidine Ce was required for light‐to‐moderate sedation (MOAA/S 3‐4), whereas a lower value than that used in the previous volunteer studies was required for deep sedation (MOAA/S ≤ 2) .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations